Co‐circulation of Peste‐des‐Petits‐Ruminants Virus Asian lineage IV with Lineage II in Nigeria. Issue 3 (12th June 2015) - Woma, T. Y.; Adombi, C. M.; Yu, D.; Qasim, A. M. M.; Sabi, A. A.; Maurice, N. A.; Olaiya, O. D.; Loitsch, A.; Bailey, D.; Shamaki, D.; Dundon, W. G.; Quan, M.
Summary: Peste‐des‐petits‐ruminants (PPR), a major small ruminant transboundary animal disease, is endemic in Nigeria. Strains of the causal agent, peste‐des‐petits‐ruminants virus (PPRV), have been differentiated into four genetically distinct lineages based on the partial sequence of the virus nucleoprotein (N) or fusion (F) genes. Peste‐des‐petits‐ruminants virus strains that were identified initially in Africa were grouped into lineages I, II and III and viruses from Asia were classified as lineage IV and referred to as the Asian lineage. Many recent reports indicate that the Asian lineage is now also present in Africa. With this in mind, this study was conducted to reassess the epidemiology of PPRV in Nigeria. A total of 140 clinical samples from 16 sheep and 63 goats with symptoms suggestive of PPR were collected from different states of Nigeria during a four‐year period (2010–2013). They were analysed by the amplification of fragments of the N gene. Results for 33 (42%) animals were positive. The phylogenetic analysis of the N gene sequences with those available in GenBank showed that viruses that were detected belong to both lineage II and IV. Based on an analysis of the N gene sequences, the lineage IV isolates grouped into two clades, one being predominant in the north‐eastern part of the country and the other found primarily in the southern regions of the country. This study reports the presence of PPRV Asian lineage IV in Nigeria for the first time.